THE RELATIONSHIP OF NURSING COMPLIANCE IN RUNNING INFUSION BASED ON STANDARD OPERATIOAL SYSTEM IN FLEBITIS EVENT CLASS 2, CLASS 3 AND EMERGENCY ROOM AT Dr. M. HASSANTOTO HOSPITAL BOGOR: HUBUNGAN KEPATUHAN PERAWAT DALAM MENJALANKAN SPO PEMASANGAN INFUS DENGAN KEJADIAN FLEBITIS DI RUANG INAP KELAS 2, KELAS 3 DAN IGD RSAU DR M. HASSANTOTO BOGOR - Al Muhajirin; Armein Sjuhary Rowi (Jurnal Ilmiah Wijaya, 2018)
According to World Health Organization (WHO) surveillance data it is stated that the incidence of nosocomial infections is quite high at 5% per year, 9 million people out of 190 million hospitalized patients. Occurrence of phlebitis becomes indicator of hospital minimum service quality with standard of incidence ≤1,5%. The purpose of the study was to analyze the relationship of nursecompliance in running SPO infusion with the incidence of phlebitis class 2, class 3 and Emegergency room at RSAU dr M. Hassan Toto Hospital Bogor. The research design used was analytic survey. Sample of this study amounted to 46 nurses obtained by Acidental Sampling. This research was conducted in March 2017. Data collection was done by observing the infusion by nurses and observation of phlebitis occurrence. The results showed 46 respondents who obtained results 22 people (84.6%) obedient and not phlebitis during hospitalization. Result of statistical test using Creamer got value P = 0,009 which mean p value ˂0,05 mean Ho rejected. From the result of the research, it can be concluded that there is nurse compliance relationship in running SPO infusion with